Faktor Kerusakan Habitat dan Sumber Air Terhadap Populasi Harimau Sumatera (Panthera tigris sumatrae Pocock, 1929) di Seksi Pengelolaan Taman Nasional (SPTN) Wilayah III Taman Nasional Sembilang - Paiman, Asrizal; Anggraini, Riana; Maijunita, Maijunita (Fakultas Kehutanan Universitas Jambi, 2018)
This research was conducted to obtain information about factors that influence habitat damage and water resources on the population of the Sumatra tiger (Panthera tigris Sumatra) in SPTN III Sembilang National Park which was one of the locations of the habitat of the Sumatran tiger. The purpose of this research are: (1) Determine the habitat damage of the Sumatran tiger (Panthera tigris Sumatra) and water resources in SPTN III Sembilang National Park. (2) Determine the population of Sumatran tiger (Panthera tigris Sumatra) in SPTN III Sembilang National Park by using camera trap. The results of this research are expected to provide information on damage to the habitat of the Sumatran tiger (Panthera tigris Sumatra) and water resources for the management of Sembilang National Park that is used as a basis in determining the actions and the conservation of forests and water sources for the population of Sumatran tiger (Panthera tigris Sumatran). Identification of tigers using camera traps. Camera trap mounted on a tree with a height of 30-45 cm from the ground up, the camera position overlooking the track at a distance of 2.5 meters. Camera trap photo printing time, temperature and date of the incident, then the data were analyzed using the software program CAPTURE Arc GIS 9.3.